Solid-State Fermentation of Plant Feedstuff Mixture Affected the Physiological Responses of European Seabass (Dicentrarchus labrax) Reared at Different Temperatures and Subjected to Salinity Oscillation - Diogo Amaral; Diogo Moreira Filipe; Thais Franco Cavalheri; Lúcia Vieira; Rui Pedro Magalhães; Isabel Belo; Helena Peres; Rodrigo O. de A. Ozório (Animals, 2023)
This study aimed to evaluate the effects of dietary inclusion of plant feedstuff mixture (PFM) pre-treated by solid-state fermentation (SSF) on the physiological responses of European seabass. For that purpose, two diets were formulated to contain: 20% inclusion level of non-fermented plant ingredients mixture (20Mix) and 20Mix fermented by A. niger in SSF conditions (20Mix-SSF). Seabass juveniles (initial body weight: 20.9 ± 3.3 g) were fed the experimental diets, reared at two different temperatures (21 and 26 °C) and subjected to weekly salinity oscillations for six weeks. Growth performance, digestive enzyme activities, humoral immune parameters, and oxidative stress indicators were evaluated. A reduction in weight gain, feed intake, and thermal growth coefficient was observed in fish fed the fermented diet (20Mix-SSF). Salinity oscillation led to an increase in weight gain, feed efficiency, daily growth index, and thermal growth coefficient, regardless of dietary treatment. Higher rearing temperatures also increased daily growth index. No dietary effect was observed on digestive enzymes activities, whereas rearing temperature and salinity oscillation modulated digestive enzyme activities. Oxidative stress responses were significantly affected by experimental diets, temperature, and salinity conditions. Catalase and glutathione peroxidase activities showed an interactive effect. Fish reared at 21 °C showed higher enzymatic activity when fed the 20Mix-SSF. Conversely, fish reared at 26 °C showed higher GPx activity when fed the 20Mix diet. Fish reared at 26 °C showed reduced peroxidase and lysozyme activities, while salinity fluctuation led to increased lysozyme activity and decreased ACH50 activity. ACH50 activity increased in fish fed the 20Mix-SSF. Overall, the dietary inclusion of PFM fermented by A. niger was unable to mitigate the impact of environmental stress on physiological performance in European seabass. In fact, fermented feed caused an inhibition of growth performances and an alteration of some physiological stress indicators.